PECULIARITIES OF RENDERING METAPHORS IN THE UKRAINIAN TRANSLATION OF THE NOVEL “THE BOOK THIEF” BY M. ZUZAK - Vyksiuk, Kh. V.; Stakhmych, Yu. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the investigation of the peculiarities of rendering metaphors in the Ukrainian translation of the novel “The Book Thief” by M. Zuzak. The existing approaches to the classification of metaphors have been described and systematized. The types of metaphors used in the novel under investigation have been analyzed. The methods of metaphor translation have been characterized. The peculiarities of translating metaphors from English into Ukrainian have been studied.